Informe descriptivo sobre la Atención Inmediata en el periodo enero a junio de 2010. - Alcaldia de Medellín, Secretaria de Bienestar Social (La Sociología en sus Escenarios, 2010)
Abstract. According to Law 387 of 1997, to Law 1190 of 2008 and Decree 1997 of 2009, the Immediate Attention is competition of the Municipality of Medellín, because the Humanitarian Attention of Emergencia and just named Humanitarian Attention of Transition is competition of Social Action. The Immediate Attention gives a: 1. Homes in displacement situation that just arrive at the city; , homes in situation of displacement also forced intra-urban just affected, that count or not on social networks in the Municipality. 2. Homes that leave shelter by fulfillment of the 23 days, or that is in valuation or not including. 3. Homes that leave shelter by social network (less than 23 days). 4. Homes that leave shelter by inclusion (This already are emergencia attention). 5. Homes with high degree of vulnerability. In addition, since the Immediate Attention is divided in Immediate Attention, Shelter and Lodging, also there are homes in shelter already temporary lodging. The present report is a net descriptive report that it has by objective to establish the efforts that the administration does based on guaranteeing the right to the minimum subsistence of the population in displacement situation. In the First part of the report one appears month to month (January-June) the total of Homes and number of people who received the Immediate Attention, with the Total Values and the concepts. Unit of Analysis and Evaluation of Public Policy 3 Secondly the report presents/displays consolidated of the deliveries for the period between the 1 of January and 25 of June, according to Homes, number of people, values and concepts in Immediate Attention, Shelter and Lodging. In the third section the consolidated one of the Immediate Attention appears according to execution of resources given until the 25 of June differentiated by concepts and number of homes; in addition it presents/displays the execution of resources with respect to the Homes sent by the Group Integral Directions and Immediate Attention. Finally the report presents/displays the Immediate Attention Shelter according to number of Homes registered in SIGMA and on the basis of Excel Data of Subcomponente de Albergue in which the homes are registered that enter Shelter, according to sex, age, the type of displacement and approach differential. Resumen. Conforme a la Ley 387 de 1997, a la Ley 1190 de 2008 y al Decreto 1997 de 2009, es competencia del Municipio de Medellín la Atención Inmediata, pues la Atención Humanitaria de Emergencia y la recién nombrada Atención Humanitaria de Transición son competencia de Acción Social. La Atención Inmediata se entrega a: 1. Hogares en situación de desplazamiento que recién llegan a la ciudad; así mismo, hogares en situación de desplazamiento forzado intraurbano recién afectados, que cuentan o no con redes sociales en el Municipio. 2. Hogares que salen de albergue por cumplimiento de los 23 días, ya sea que estén en valoración o no incluidos. 3. Hogares que salen de albergue por red social (menos de 23 días). 4. Hogares que salen de albergue por inclusión (Esto ya es atención de emergencia). 5. Hogares con alto grado de vulnerabilidad. Además, dado que la Atención Inmediata se divide en Atención Inmediata, Albergue y Alojamiento, también hay hogares en albergue ya alojamiento temporal. El informe presente es un informe netamente descriptivo que tiene por objetivo establecer los esfuerzos que la administración hace en función de garantizar el derecho a la subsistencia mínima de la población en situación de desplazamiento. En la Primera parte del informe se presenta mes a mes (Enero-Junio) el total de Hogares y número de personas que recibieron la Atención Inmediata, con los Valores Totales y los conceptos. Unidad de Análisis y Evaluación de Política Pública 3 En segundo Lugar el informe presenta un consolidado de las entregas para el periodo entre el 1 de Enero y el 25 de Junio, según Hogares, número de personas, valores y conceptos en Atención Inmediata, Albergue y Alojamiento. En el tercer apartado se presenta el consolidado de la Atención Inmediata según ejecución de recursos entregados hasta el 25 de Junio diferenciado por conceptos y número de hogares; además presenta la ejecución de recursos respecto de los Hogares remitidos por la Orientaciones Integrales Grupales y Atención Inmediata. Por último el informe presenta la Atención Inmediata Albergue según número de Hogares registrados en SIGMA y en base de Datos Excel del Subcomponente de Albergue en la que se registran los hogares que ingresan a Albergue, según sexo, edad, el tipo de desplazamiento y enfoque diferencial.